2020
DOI: 10.1038/s41392-020-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Twist1-induced miR-199a-3p promotes liver fibrosis by suppressing caveolin-2 and activating TGF-β pathway

Abstract: The activation of hepatic stellate cells (HSCs) participates in liver fibrosis, and emerging evidences indicate that microRNAs (miRNAs) are abnormally expressed during HSC activation. However, the potential roles of miRNAs in liver fibrosis still remain elusive. Therefore, this study aimed to investigate the role of miR-199a-3p in liver fibrosis and its underlying mechanism. We found that miR-199a-3p expression was dramatically upregulated during HSC activation in vitro, and during liver fibrogenesis in CCl 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…ASTEX were deficient in proinflammatory and profibrotic miRs including miR-199a, miR-143, miR-382, and miR-134 ( Figure 3C ). MiR-199a promotes fibrosis through suppression of caveolin and induction of the TGFβ pathway ( Yang et al, 2020 ). MiR-143 also promotes fibrosis through targeting sprouty RTK signaling antagonist 3 (Spry3) to activate the p38-ERK-JNK signaling axis ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…ASTEX were deficient in proinflammatory and profibrotic miRs including miR-199a, miR-143, miR-382, and miR-134 ( Figure 3C ). MiR-199a promotes fibrosis through suppression of caveolin and induction of the TGFβ pathway ( Yang et al, 2020 ). MiR-143 also promotes fibrosis through targeting sprouty RTK signaling antagonist 3 (Spry3) to activate the p38-ERK-JNK signaling axis ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, accumulating evidences have suggested that miRNAs play important roles and might be regarded as a potential therapeutic target in regulating the progression and development of several liver diseases (13)(14)(15)(16). Previous reports have demonstrated that there were increased levels of miR-130a-3p in myocardial injury, and downregulation of miR-130a-3p could remarkably relieve hypoxia-induced inflammation and inhibit the expression of fibrosis-related protein (17).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the miRNAs that regulate HSCs phenotype were consistently reversed with a concomitant decrease in hepatic ECM deposition. miRNAs that activate HSCs (miR-199a-3p and miR-214-3p) were significantly suppressed (Ma et al, 2018;Yang et al, 2020), while those restrain the proliferation and activation of HSCs (miR-378a-3p, miR-139-5p, miR-455-3p, and miR-193a-3p) were remarkably increased during the fibrosis regression (Hyun et al, 2016;Ju et al, 2019;Wei et al, 2019;He et al, 2021). Among the differentially (mmu-miR-1843a-5p, mmu-miR-193a-5p, mmu-miR-194-2-3p, and mmu-miR-30c-2-3p) and their target genes.…”
Section: Discussionmentioning
confidence: 99%